Religious Moderation from an Islamic Perspective and Its Implementation in Islamic Boarding Schools - Hana Wilda Tazkiya (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
Religious moderation is a view that is not too excessive, not radical, and not extreme. Islamic boarding schools are traditional Islamic educational institutions that focus on learning Islam and its application in everyday life, a common view. The method used in this article is a qualitative method, namely interpreting and understanding specific documents or texts. The data sources used are books and scientific journals. This study aims to explain the Islamic perspective on religious moderation and its implementation in Islamic boarding schools. The results show that the values of moderation are actually developed in these Islamic boarding schools, including tawassuth (moderation in worship), i'tidal (justice), tasamuh (tolerance), tawazun (balance), musawah (equality), and shura (deliberation).